2005
DOI: 10.1038/sj.bmt.1704889
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral T-cell expansion and low infection rate after reduced-intensity conditioning and allogeneic blood stem cell transplantation

Abstract: Summary:Peripheral blood stem cell transplantation after reducedintensity conditioning (RIC-PBSCT) regimen is an alternative to conventional regimens with less immediate toxicity. Since immune recovery is of crucial importance for the control of infections, we retrospectively studied the recovery of T-, B-and NK cell subsets in 20 consecutive patients undergoing RIC-PBSCT. We also studied the thymic output using T-cell receptor excision circle assay. Engraftment was rapid and few infectious complications were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 39 publications
1
17
1
Order By: Relevance
“…In support of this hypothesis, emerging data also reveal that graft-versus-host disease is greater in the setting of impaired thymopoiesis. 2,[45][46][47] Studies also suggest that reduced intensity regimens may permit greater thymic renewal after transplant, 48,49 presumably as a result of TEC preservation. In addition to a selective loss of UEA ϩ TEC, our data suggest that renewal of thymopoiesis may be impaired because of diminished CCL25 production and inability to mediate ETP uptake and augment early DN development, restricting niche availability.…”
Section: Ccl25 Increases Thymopoiesis After Castration 3261mentioning
confidence: 99%
“…In support of this hypothesis, emerging data also reveal that graft-versus-host disease is greater in the setting of impaired thymopoiesis. 2,[45][46][47] Studies also suggest that reduced intensity regimens may permit greater thymic renewal after transplant, 48,49 presumably as a result of TEC preservation. In addition to a selective loss of UEA ϩ TEC, our data suggest that renewal of thymopoiesis may be impaired because of diminished CCL25 production and inability to mediate ETP uptake and augment early DN development, restricting niche availability.…”
Section: Ccl25 Increases Thymopoiesis After Castration 3261mentioning
confidence: 99%
“…The signal-joint TRECs were quantified in peripheral blood mononuclear cells using real-time quantitative PCR on LightCycler (Roche Diagnostics, Meylan, France), as described previously. 27 A series of standard dilutions of a plasmid containing the signal-joint breakpoint was used to quantify TRECs in each patient and control DNA sample. Cycle threshold was assessed using the second derivative method with the LightCycler 3.5.3 software (Roche Diagnostics).…”
Section: Trec Analysismentioning
confidence: 99%
“…Unfortunately, toxic affects together with the immunodeficiency early post-transplant has been associated with significant transplant related morbidity and mortality and therefore reduced intensity conditioning (RIC) regimens have been increasingly investigated [(5) reviewed in (6)(7)(8)(9)]. Experimental transplant models have demonstrated that RIC regimens ('mini' HCT) show promise in lowering the incidence of complications which arise following ablative conditioning, including infection and graft-versus-host disease (GVHD) (9)(10)(11)(12). However, control of graft rejection will remain a crucial factor in determining how 'mild' a level of immunosuppression can be administered which will continue to permit successful long-term engraftment.…”
Section: Introductionmentioning
confidence: 99%